Strategi Manajemen Keuangan Rumah Tangga Pasca Pandemi Covid-19 - Lukman Hakim; Dito Wahyutomo; Dewi oktayani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Household financial management is a crucial factor in maintaining family financial stability, particularly in the face of economic uncertainty. This study examines the strategies employed by households in managing their finances, including budgeting, expenditure control, savings, and investment, as well as the challenges encountered during economic crises. Through a combination of literature review and case studies, the research reveals that households with clear financial planning and adequate emergency funds are more resilient in times of crisis, such as the COVID-19 pandemic. Factors such as income levels, education, and financial literacy significantly influence household financial decisions, while consumption patterns driven by social media often present a challenge. Effective strategies identified include strict budgeting, reducing non-essential expenditures, and prioritizing long-term savings and investments. This study underscores the importance of financial literacy and awareness in household financial management as key to achieving financial stability amidst global and domestic economic uncertainties.